Resveratrol suppresses malignant progression of oral squamous cell carcinoma cells by inducing the ZNF750/RAC1 signaling pathway. Issue 1 (1st January 2021) - Xiao, Yue; Duan, Yanjun; Wang, Yongjie; Yin, Xiaojia
ABSTRACT: This study examined whether activation of zinc finger protein 750/Ras-related C3 botulinum toxin substrate 1 (ZNF750/RAC1) signaling pathway may be involved in the ability of resveratrol to inhibit malignant progression of CAL-27 oral squamous cell carcinoma cells. CAL-27 cells were treated with resveratrol and transfected with plasmids expressing a ZNF750 mimic or ZNF750 inhibitor. Cell proliferation and apoptosis were assessed. Western blotting was used to examine the effects of resveratrol on levels of angiogenin, vascular endothelial growth factor (VEGF), prolyl hydroxylase 2 (PHD2), G protein signal-regulated protein 5 (RGS5), integrin A5 (ITGA5), integrin B1 (ITGB1), CD44, RAC1, and ZNF750. Quantitative PCR was used to examine the effects on mRNA levels of platelet-derived growth factor (PDGFB), tumor vascular marker CD105, and cell adhesion molecules ITGA5, ITGB1, and CD44. Resveratrol downregulated angiogenin, VEGF, RGS5, CD105, and the cell adhesion molecules ITGA5, ITGB1, and CD44 expressions to inhibit the vascular normalization, metastasis, adhesion, and migration of CAL-27 cells. Conversely, it upregulated ZNF750, PHD2, and PDGFB to suppress the malignant progression of CAL-27 cells. We further observed that these changes were associated with reduced proliferation, reduced colony formation, and increased apoptosis in cancer cells. ZNF750 silencing partly reversed these effects of resveratrol on the proliferation and apoptosis of CAL-27 cells. Additionally, RAC1 agonist also weakened these impacts of resveratrol on the growth of CAL-27 cells. The ability of resveratrol to suppress the progression of oral squamous cell carcinoma may involve activation of the ZNF750/RAC1 signaling pathway and modification of the tumor vascular microenvironment. Graphical abstract: uf0001